2020
DOI: 10.7759/cureus.12365
|View full text |Cite
|
Sign up to set email alerts
|

Organizing a Mass Gathering Amidst a Rising COVID-19 Public Health Crisis: Lessons Learned From a Chinese Public Health Forum in Vancouver, BC

Abstract: IntroductionThe coronavirus disease 2019 (COVID-19) evolved from a rising public health concern to a pandemic over mere weeks. Before March 11, 2020, the Public Health Agency of Canada had not advised against any mass gatherings. Herein, we highlight practical precautions taken by event organizers to adapt to the rising public health threat from COVID-19 and maintain public safety when conducting a health forum for the Chinese community of Vancouver, British Columbia on February 22, 2020. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The maintenance, conservation, and inspection of the closed indoor building where these MGEs took place should also be strengthened. We must highlight that MEGs have continued to be held successfully with measures in place to prevent SARS-CoV-2 transmission, suggesting that MGEs could be implemented again with specific prevention measures [ 108 112 ]. Second, COVID-19 patients should be monitored to find out about this new disease and its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance, conservation, and inspection of the closed indoor building where these MGEs took place should also be strengthened. We must highlight that MEGs have continued to be held successfully with measures in place to prevent SARS-CoV-2 transmission, suggesting that MGEs could be implemented again with specific prevention measures [ 108 112 ]. Second, COVID-19 patients should be monitored to find out about this new disease and its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most articles studying COVID-19 in mass gathering events either reported retrospective analyses of SARS-CoV-2 transmission17–19 or described mitigation plans and measures applied during mass gathering events 20 21. Only one controlled trial was published in Catalonia 13…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In fact, the available evidence suggests that the risk of infection transmission significantly enhances with the duration of exposure, location (indoor > outdoor), and non-adherence with the standard prevention and control measures. [2,8] It is the need of the hour to employ the agglomeration scale and correlate the same with the occurrence of outbreaks and epidemics in heterogeneous settings. [9] More often than not, it has been reported that the chances of occurrence an outbreak of the COVID-19 infection significantly increases with agglomeration of susceptible individuals, more so in cases of urban settings.…”
Section: Covid-19 Infection and Gatheringmentioning
confidence: 99%
“…[1] The very fact that the disease spreads from one person to another by means of close contact reinforces the need to maintain physical distancing and strictly adhere to the infection prevention and control measures. [2] The purpose of the current review was to explore the significance of gatherings in COVID-19…”
Section: Introductionmentioning
confidence: 99%